The Role of the Police Intelligence Unit in the Investigation of Murder Crimes (Case Study at the Natuna Police Resort) - Iqbal, Muhammad; Laksana, Andri Winjaya (Jurnal Hukum Khaira Ummah, 2025)
This study examines the role and effectiveness of the Natuna Police Intelligence Unit (Satintelkam) in investigating murder crimes, with a focus on operational challenges in the archipelago. An empirical legal approach is used to analyze the gap between the normative mandate (Law Number 2 of 2002 and Regulation of the Chief of Police Number 10 of 2010) and implementation in the field, covering social, geographical, and institutional dynamics in Natuna Regency. The results of the study show that Satintelkam plays a strategic role    through method Human Intelligence (HUMINT), Signal Intelligence (SIGINT), and Open Source Intelligence (OSINT), which contribute to the identification of perpetrators, mapping of crime motives, and reconstruction of crime scenes, as seen in the cases of KM Samudra and Bunguran Timur. However, its effectiveness faces structural obstacles such as limited forensic technology, lack of certified human resources, and geographical barriers. Analysis based on the theory of authority, Friedman's legal system, and legal certainty reveals the disparity between ideal capacity and operational reality, which has an impact on the principle of speedy justice and the validity of evidence. The study recommends strengthening human resource capacity, procuring forensic tools, and improving cross-agency coordination (TNI AL, Immigration) to optimize intelligence functions. Local context-based solutions, such as mobile investigative units and specialized training, are proposed to mitigate geographic challenges and strengthen the integration of intelligence systems in the criminal justice process.